National Bank of Kuwait - Mariam AL-Hajri; Maria Alejandra Jaramillo Serna; Qout AL-Mutairi; Ghalia Al-Qenaei (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2019)
The national bank of Kuwait was set up in 1952 as not only the first local bank but also the first shareholding company in the state of Kuwait. Thus far, NBK has set up 162 branches across 15 countries. Also, the international expansion opportunities in the state of Kuwait, NBK is among the most profitable bank. Over the year, NBK has been consistently ranked among the top 50 safest banks in the world. NBK has established strategic client relationships which have enabled it to increase its client base across the state and also in the region. The bank avails a wide range of financial and investment products and services to its individual, corporate and institutional clients. Based on the that, partnering with NBK as a digital marketing agency can help propel further recognition of NBK which will then translate to increase in its growth and profit rates.